1974
DOI: 10.1021/ja00816a018
|View full text |Cite
|
Sign up to set email alerts
|

Triarylphosphine, hydride, and ethylene complexes or rhodium(I) chloride

Abstract: Physical studies, combining molecular weights, 31P, 13C, and 'H nmr, infrared, and spectrophotometric measurements, have been made to define the species and rates and equilibria of reactions in solutions con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
1

Year Published

1975
1975
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(97 citation statements)
references
References 0 publications
6
90
0
1
Order By: Relevance
“…This surprising observation is explained by the generation of catalytically less active dimeric rhodium species in solution under hydrogen pressure. [142] In an interphase, however, this dimerization process is prevented or at least impeded, as the monomeric rhodium(i) complex centers are spatially isolated in the stationary phase…”
Section: Hydrogenationmentioning
confidence: 99%
“…This surprising observation is explained by the generation of catalytically less active dimeric rhodium species in solution under hydrogen pressure. [142] In an interphase, however, this dimerization process is prevented or at least impeded, as the monomeric rhodium(i) complex centers are spatially isolated in the stationary phase…”
Section: Hydrogenationmentioning
confidence: 99%
“…Magnetisation transfer from the hydride ligands of these complexes into the alkyl group of the hydrogenation product is also observed. 3 ] are observed in addition to the corresponding binuclear alkene±dihydride products. The higher initial activity of these precursors is offset by the formation of the trirhodium phosphide bridged deactivation product, [{(H)(PPh 3 )Rh(m-H)(m-I)(matures and pressures, [2,3] and although the slow reduction of unsaturated alkenes by H 2 in the presence of metal ions such as Ag + or Cu 2 + was already known, [4] [RhCl(PPh 3 3 ] is capable of promoting selective hydrogenation of C=C or CC groups in the presence of other easily reducible functionalities such NO 2 or CHO.…”
Section: Introductionmentioning
confidence: 99%
“…1 show that the "P,RhClW polymers B(n,m) are generally considerably more active than their "P4Rh,C1," analogues C(n,m). In homogeneous solution the catalytic activity of [(C,H,),P],RhCl appears to be The dimer itself is described as a good hydrogenation catalyst (19) but with little substantiation. We have shown that model complexes for the silicone polymers B, C, and D, L3RhCl and L4Rh,Cl, (20) (L = [(CH3)3SiO],Si(CH3)CH2CHzP(C6H5)2) are both active catalysts for styrene hydrogenation with the dimer being less active.…”
Section: )mentioning
confidence: 99%